Synthesis and characterization of magnetite and magnetite/starch nanocomposite thin films for electrochemical applications - Khoh, Wai Hwa. (Universiti Malaysia Sarawak (UNIMAS), 2011)
The aims of this study were to investigate the effects of synthesis conditions on the capacitive behaviors of magnetite and magnetite/starch nanocomposite thin films. In addition, the relationship between the microstructure of thin films and their electrochemical properties was elucidated. Magnetite nanocomposite in the form of stable colloidal suspension was synthesized by the co-precipitation of Fe (II) and Fe (III) ions in the ammonium hydroxide solution at 80% under inert atmosphere. Nanocomposite of magnetic/starch nanocomposites in the form of colloidal suspension were synthesized by the same co-precipitation approach in the presence of dissolved starch in different aqueous solvent such as NH4OH and NaOH (6 wt %) /urea ( 5wt %).